2016
DOI: 10.1038/srep34759
|View full text |Cite
|
Sign up to set email alerts
|

Feature Subset Selection for Cancer Classification Using Weight Local Modularity

Abstract: Microarray is recently becoming an important tool for profiling the global gene expression patterns of tissues. Gene selection is a popular technology for cancer classification that aims to identify a small number of informative genes from thousands of genes that may contribute to the occurrence of cancers to obtain a high predictive accuracy. This technique has been extensively studied in recent years. This study develops a novel feature selection (FS) method for gene subset selection by utilizing the Weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, our numerical experiments revealed that the prediction performance of RF strongly depended on the input variables ( Figure S4), indicating that feature selection before the RF should be designed carefully. SVM can be used for feature selection 30 . An SVM has been used for breast cancer diagnosis 31 and used with feature selection, such as the use of k-mean clustering, before training of a model 32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our numerical experiments revealed that the prediction performance of RF strongly depended on the input variables ( Figure S4), indicating that feature selection before the RF should be designed carefully. SVM can be used for feature selection 30 . An SVM has been used for breast cancer diagnosis 31 and used with feature selection, such as the use of k-mean clustering, before training of a model 32 .…”
Section: Discussionmentioning
confidence: 99%
“…(i) F-test [72], which is a traditional filter-based gene selection method, it uses the statistical hypothesis testing (ii) RLR [73], which is based on linear discriminant analysis criterion. The class centroid is estimated to define both the between-class separability and the within-class compactness (iii) WLMGS (Weight Local Modularity based Gene Selection) [74], which uses the weight local modularity of a weighted sample graph to evaluate the discriminative power of gene subset (iv) LNNFW [75], which uses the k-nearest neighbors rule to minimize the within-class distances and maximize the between-class distances [20], which is based on subspace learning and manifold regularization (vi) AHEDL [22], which is based on dictionary learning theory with adaptive hypergraph learning and regularization…”
Section: Experimental Settingsmentioning
confidence: 99%
“…In case of [ 16 ], the genetic algorithm-based feature selection method was applied to improve the decision-making process considering the tissue image of breast cancer patients. To find the set of genes for cancer classification, the quantum-behaved binary particle swarm optimization (BPSO) [ 17 ], the forward search method considering the weight local modularity [ 18 ], and the kernel-based clustering method for gene selection using double radial basis function kernels [ 19 ] were suggested. On the other hand, the identification methods of cancer-driving variants were developed by considering mutation timing of variants [ 20 ] and utilizing the gradient tree boosting and iterative search method [ 21 ].…”
Section: Introductionmentioning
confidence: 99%